Skeletal Status, Body Composition, and Glycaemic Control in Adolescents with Type 1 Diabetes Mellitus - Elzbieta Wierzbicka; Anna Swiercz; Pawel Pludowski; Maciej Jaworski; Mieczyslaw Szalecki (Journal of Diabetes Research)
Background. Disturbed bone turnover, osteoporosis, and increased fracture risk are late complications of insulin-dependent diabetes mellitus. Little is known about how far and to what extent can glycaemic control of type 1 diabetes mellitus (T1DM) prevent disturbances of bone health and body composition during the growth and maturation period. Objective. The aim of this cross-sectional study was to compare the skeletal status outcomes and body composition between patients stratified by glycaemic control (1-year HbA1c levels) into well- and poorly-controlled subgroups in a population of T1DM adolescents, that is, <8% and ≥8%, respectively. Subjects and Methods. Skeletal status and body composition were evaluated in 60 adolescents with T1DM (53.3% female; mean aged: 15.1 ± 1.9 years; disease duration: 5.1 ± 3.9 years) using dual energy X-ray absorptiometry (GE Prodigy). The results were compared to age- and sex-adjusted reference values for healthy controls. The calculated Z-scores of different metabolic control subgroups were compared. Clinical data was also assessed. Results. As evidenced by Z-scores, patients with T1DM revealed a significantly lower TBBMD (total body bone mineral density), TBBMC (total body bone mineral content), S24BMD (bone mineral density of lumbar spine L2–L4), and TBBMC/LBM ratio (total body bone mineral content/lean body mass), but higher FM (fat mass) and FM/LBM ratio (fat mass/lean body mass) values compared to an age- and sex-adjusted general population. The subset (43.3% patients) with poor metabolic control (HbA1c ≥ 8%) had lower TBBMD, TBBMC, and LBM compared to respective values noted in the HbA1c < 8% group, after adjusting for confounders (mean Z-scores: −0.74 vs. −0.10, p=0.037; −0.67 vs. +0.01, p=0.026; and −0.45 vs. +0.20, p=0.043, respectively). Additionally, we found a significant difference in the TBBMC/LBM ratio (relative bone strength index) between the metabolic groups (−0.58 vs. −0.07; p=0.021). A statistically significant negative correlation between 1-year HbA1c levels and Z-scores of TBBMD, TBBMC, and LBM was also observed. In patients with longer disease duration, a significant negative correlation was established only for TBBMD, after adjusting for confounders. The relationships between densitometric values and age at onset of T1DM and sex were not significant and showed no relation to any of the analysed parameters of the disease course. Conclusion. Findings from this study of adolescents with T1DM indicate that the lower Z-scores of TBBMD, TBBMC, and LBM as well as the TBBMC/LBM ratio are associated with increased HbA1c levels. Their recognition can be crucial in directing strategies to optimise metabolic control and improve diabetes management for bone development and maintenance in adolescents with T1DM.